Freeze/Thaw-Induced Embolism: Probability of Critical Bubble Formation Depends on Speed of Ice Formation - Sevanto, Sanna; Holbrook, Noel Michele; Ball, Marilyn (Frontiers in Plant Science, 2012)
Bubble formation in the conduits of woody plants sets a challenge for uninterrupted water transportation from the soil up to the canopy. Freezing and thawing of stems has been shown to increase the number of air-filled (embolized) conduits, especially in trees with large conduit diameters. Despite numerous experimental studies, the mechanisms leading to bubble formation during freezing have not been addressed theoretically. We used classical nucleation theory and fluid mechanics to show which mechanisms are most likely to be responsible for bubble formation during freezing and what parameters determine the likelihood of the process. Our results confirm the common assumption that bubble formation during freezing is most likely due to gas segregation by ice. If xylem conduit walls are not permeable to the salts expelled by ice during the freezing process, osmotic pressures high enough for air seeding could be created. The build-up rate of segregated solutes in front of the ice-water interface depends equally on conduit diameter and freezing velocity. Therefore, bubble formation probability depends on these variables. The dependence of bubble formation probability on freezing velocity means that the experimental results obtained for cavitation threshold conduit diameters during freeze/thaw cycles depend on the experimental setup; namely sample size and cooling rate. The velocity dependence also suggests that to avoid bubble formation during freezing trees should have narrow conduits where freezing is likely to be fast (e.g. branches or outermost layer of the xylem). Avoidance of bubble formation during freezing could thus be one piece of the explanation why xylem conduit size of temperate and boreal zone trees varies quite systematically.